2003
DOI: 10.1242/dev.00319
|View full text |Cite
|
Sign up to set email alerts
|

A mosaic genetic screen for genes necessary forDrosophilamushroom body neuronal morphogenesis

Abstract: Neurons undergo extensive morphogenesis during development. To systematically identify genes important for different aspects of neuronal morphogenesis, we performed a genetic screen using the MARCM system in the mushroom body (MB) neurons of the Drosophila brain. Mutations on the right arm of chromosome 2 (which contains ~20% of the Drosophila genome) were made homozygous in a small subset of uniquely labeled MB neurons. Independently mutagenized chromosomes (4600) were screened, yielding defects in neuroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 42 publications
3
61
0
1
Order By: Relevance
“…Alternatively, these ectopic synapses might result from a defect in either synaptic targeting or nerve sprouting. Consistent with this idea, we note the ectopic synapse is reminiscent of aberrant axonal projections in the visual system Senti et al, 2003) and the mushroom body in the fmi mutant (Reuter et al, 2003) and in the brain and spinal cord of Celsr3-deficient mice (Tissir et al, 2005). Hence, Flamingo likely also regulates both synaptic target selection and axonal projection at the NMJ.…”
Section: Flamingo Is Crucial For Both Target Selection and Synaptogensupporting
confidence: 74%
See 2 more Smart Citations
“…Alternatively, these ectopic synapses might result from a defect in either synaptic targeting or nerve sprouting. Consistent with this idea, we note the ectopic synapse is reminiscent of aberrant axonal projections in the visual system Senti et al, 2003) and the mushroom body in the fmi mutant (Reuter et al, 2003) and in the brain and spinal cord of Celsr3-deficient mice (Tissir et al, 2005). Hence, Flamingo likely also regulates both synaptic target selection and axonal projection at the NMJ.…”
Section: Flamingo Is Crucial For Both Target Selection and Synaptogensupporting
confidence: 74%
“…Defects in axonal projections in fmi mutants have been implicated at the embryonic NMJ and shown in sensory cells (Sweeney et al, 2002), in the fly visual system Senti et al, 2003), and mushroom bodies (Reuter et al, 2003). Additionally, mice deficient in Celsr3 have also been shown to have aberrant and overgrown axons in the brain and spinal cord (Tissir et al, 2005).…”
Section: Fmi Mutations Promote the Formation Of Ectopic Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work showed that Flamingo acts probably through two different mechanisms to regulate dendritic field formation [23] . At the initial stage, Using a mosaic genetic screen, flamingo has been found to regulate axonal projection in addition to suppressing dendritic overextension [24] . Flamingo overexpression in the mushroom body results in loss of the dorsal branches of axons.…”
Section: Flamingo and Neuronal Morphogenesismentioning
confidence: 99%
“…In this way, only the mutant neurons are labeled and their morphology can be analyzed. Notably, the shot 3 mutant allele was the first ever mutant allele used for MARCM analyses, which have revealed Shot requirements during axon growth and neuronal polarity at pupal stages (Lee & Luo, 1999;Reuter, 2003. …”
Section: P0145mentioning
confidence: 99%